INCREASING PRODUCTION OF RICE CROPS AND NILA FISH THROUGH APPLICATION OF THE MINAPADI AND JAJAR LEGOWO SYSTEM ON SWAMP LAND - Soeparjono, Sigit (Jurnal Agrotek Tropika, 2025)
Rice cultivation in Indonesia, especially in swamplands, is still relatively small and less popular, this is due to farmers' lack of understanding in applying cultivation technology and the low production obtained so that it provides less profit for rice farmers. The presence of fish in the Minapadi system is thought to influence rice growth and production. The Minapadi farming system is a way of rearing (cultivating) fish with rice or raising fish in between rice plants. This is intended so that the profits obtained from this business have double results, namely: from the rice itself and from the fish on the other hand. This research used an experimental method with a factorial randomized block design which was repeated 3 times divided into two series of experiments, namely: Experiment series 1 was a factorial experiment (3x3) consisting of factor A (Jarwo) with levels (A1) Jarwo 4:1, (A2 ) Jarwo 3:1, (A3) Jarwo 2:1. Factor B (Planting distance) with levels (B1) 20x20 cm, (B2) 20x25 cm, (B3) 20x30 cm. Experiment series 2 is a factorial experiment (3x3) consisting of factor B (Planting distance) with levels (B1) 20x20 cm, (B2) 20x25 cm, (B3) 20x30 cm. Factor C (tilapia fish population) with levels (C1) 25 fish/plot, (C2) 50 fish/plot, (C3) 75 fish/plot with a plot size of 5x10 m. Based on the data from statistical analysis, it was concluded that the combination of Jajar Legowo treatment with planting distance and the best results were shown by Jajar Legowo (4:1) with a planting distance of 20x30 cm, but the highest grain weight per plant was shown by the combination of Jajar Legowo treatment (2: 1) with a planting distance of 20x25 cm and the effect of the treatment interaction between planting distance and fish population has a real influence on the parameters of fish weight, fish length, fish weight per plot and number of fish per plot. The combination treatment with a planting distance of 20x30 cm with a fish population of 75 fish per plot gave the best results for all dead parameters.